DETERMINAN JUMLAH KREDIT YANG DISALURKAN (Studi Kasus pada Bank Umum di Indonesia) (Students' Journal of Accounting and Banking, 2013)
Types of data that was used are data time series from 2007 to 2011 with N = 60. Sampling technique using census method which all the whole general bank that operated in Indonesia in the that period are included in object research, and by using a statistical method, so called multiple linear regression, to attest the proposed hypothesis. In hypothesis test, there are three subtests that help the researcher in analyzing and inferring the data and its behavior. First, T-test is for checking the significance of individual regression coefficients. Second, coefficient of determination, denoted by R2, indicates how far the ability of the model in explaining the dependent variable. Third, F-Statistics attempts to test the influence of the overall variables simultaneously.Based on the results of this study concluded that: (1) Third Party Funds (DPK) significantly positive effect to the amount of bank credit. Much higher the amount of Third Party Fund, much bigger the credit given to a company or individual. Whilst, (2) Capital Adequacy Ratio (CAR) gives significantly negative effect to the amount of bank credit. Much higher the CAR is not followed by an increasing amount of bank credit. 3) Return on Assets (ROA) was not a significantly positive effect to the amount of bank credit The  higher the ROA lending also increased. (4) Non-Performing Loan (NPL) gives not a significantly negative effect on amount of bank credit. The lower NPL will encourage an increase in the number of loans disbursed. (5) Interest rate of Bank Indonesia Certificates (SBI) gives significant positive effect on amount of bank credit. The higher the interest rate of SBI is likely to encourage amount of bank credit.Keywords: Third Party Fund (DPK), Capital Adequacy Ratio (CAR), Return on Asset (ROA), Non Performing Loan (NPL), the interest rate of Bank Indonesia Certificate (SBI) and Bank Credit.